The image of Islamic jihad and prophet's warfare in the west between myth and reality - Osmani, Noor Mohammad (s.n, 2012)
A global concern about Islam has been drastically increasing along with some pertinent events in the last few decades. Eventually, the occurrences of 9/11, Middle East issue, Iraq, Afghanistan and other countries have ignited this interest of a great extent among the masses around the globe.